With Dual Mediation Mechanism Unpacking the Impact of Digital Leadership on Innovative Work Behavior - Ihsan Ul Haq; Umar Farooq; Usman Nasir; Hasina Khatoon; Syed Taqi Ul Hassan; Abdu Saboor; Faiza Shafi (Indus Journal of Social Sciences, 2025)
Organizations are working to innovate in the age of digital transformation. According to shifts in management environments, which are closely linked to creative work practices, leadership is specifically evolving into digital leadership. This study clarified the role of digital culture and employees’ digital capabilities in perspectives on digital leadership by focusing on employees’ innovative work behaviors. Using a survey focused on digital leadership, digital culture, employees’ digital capabilities, and employees’ innovative work behaviors, this study gathered data from 295 employees working for Pakistani companies. It then used SPSS software to test its hypotheses. The findings demonstrate that innovative work practices are positively impacted by digital leadership both directly and indirectly. Furthermore, the relationship between digital leadership and creative work practices in Pakistan is partially mediated by digital culture and employees’ digital capabilities. By demonstrating the importance of digital leadership in creative work practices, this study advances the field of leadership and resource-based view (RBV) research.